Hearing Loss Assessment: Evaluating The Uhear Tm An Ios-Based Application As A Screening Tool. - Stephen Agbomhekhe Ogah (ziauddin University, 2024)
Background: Disabling hearing loss is a major health issue all over the world. It is however found to be worse in the developing countries according to WHO. It is said that one in five Africans now operate smartphones which can be effectively use for hearing loss screening purposes. The purpose of the study is to evaluate the use of uHearTM an iOS-based application on iPhone as a hearing loss screening tool. Methods: This is a prospective hospital base study carried out in ENT clinic between January 2014 and December 2015 after obtaining the hospital ethical committee approval. Consented adults that could operate iphone were recruited for the study by convenience sampling. Subjects had a conventional audiometric test after which they were made to complete the iPhone uHearTM test using the headphones supplied with the device in a quiet room. Hearing loss at frequencies of 250Hz-8000Hz were determined with a threshold of >40 dB considered as 'Failed screening' and a p-value of <0.05 was considered significant. Results: Ninety eight ears of 49 patients were tested, males 26 and females 23 with male to female ratio of 1.1:1. There was a statistically significant difference between pure tone thresholds recorded with the iPhone and that of the audiometer at lower frequencies. However, there was no statistically significant difference between these thresholds recorded at higher frequencies. Conclusion: The uHearTM 'app' on iPhone is effective in detecting high-frequency hearing loss, and can be use in hearing loss screening programmes. Key Words: uHearTM, iPhone, hearing, screening, tool.